Hybrid Polymer Composite Materials - Properties and Characterisation - Thakur, Vijay Kumar; Thakur, Manju Kumari; Pappu, Asokan (Elsevier, 2017)
This book presents the latest on these composite materials that can best be described as materials that are comprised of synthetic polymers and biological/inorganic/organic derived constituents. The combination of unique properties that emerge as a consequence of the particular arrangement and interactions between the different constituents provides immense opportunities for advanced material technologies. This series of four volumes brings an interdisciplinary effort to accomplish a more detailed understanding of the interplay between synthesis, structure, characterization, processing, applications, and performance of these advanced materials, with this volume focusing on their properties and characterization.